Genetic variability of the core protein in hepatitis C virus genotype 4 in Saudi Arabian patients and its implication on pegylated interferon and ribavirin therapy - Alhamlan, Fatimah S (BioMed Central, 2014)
BACKGROUND: Hepatitis C virus (HCV) shows a remarkable genetic diversity, contributing to its high persistence and varied susceptibilities to antiviral treatment. Previous studies have reported that the substitution of amino acids in the HCV subgenotype 1b core protein in infected patients is associated with a poor response to pegylated interferon and ribavirin (PEG-IFN/RBV) combined therapy. OBJECTIVES: Because the role of the core protein in HCV genotype 4 infections is unclear, we aimed in this study to compare the full-length core protein sequences of HCV genotype 4 between Saudi patients who responded (SVR) and did not respond (non-SVR) to PEG-IFN/RBV therapy. STUDY DESIGN: Direct sequencing of the full-length core protein and bioinformatics sequence analysis were utilized. RESULTS: Our data revealed that there is a significant association between core protein mutations, particularly at position 70 (Arg(70)Gln), and treatment outcome in HCV subgenotype 4d patients. However, HCV subgenotype 4a showed no significant association between core protein mutations and treatment outcome. In addition, amino acid residue at position 91 was well-conserved among studied patients where Cys(91) is the dominant amino acid residue. CONCLUSIONS: These findings provide a new insight into HCV genotype 4 among affected Saudi population where the knowledge of HCV core gene polymorphisms is inadequate.